Health risk characterization for exposure to benzene in service stations and petroleum refineries environments using human adverse response data. (2015) - Edokpolo, Benjamin; Yu, Qiming Jimmy; Connell, Des
Abstract: Health risk characterization of exposure to benzene in service stations and petroleum refineries has been carried out in previous studies using guideline values set by various agencies. In this work, health risk was characterized with the exposure data as cumulative probability distribution (CPD) plots but using human epidemiological data. This was achieved by using lowest observable adverse effects levels (LOAEL) data plotted as cumulative probability lowest effects distribution (CPLED). The health risk due to benzene was characterized by using probabilistic methods of hazard quotient (HQ50/50 and HQ95/5 ), Monte-Carlo simulation (MCS) and overall risk probability (ORP). CPD relationships of adverse health effects relationships and exposure data were in terms of average daily dose (ADD) and lifetime average daily dose (LADD) for benzene. For service station environments HQ50/50 and HQ95/5 were in a range of 0.000071–0.055 and 0.0049–21, respectively. On the other hand, the risk estimated for petroleum refinery environments suggests higher risk with HQ50/50 and HQ95/5 values ranging from 0.0012 to 77 and 0.17 to 560, respectively. The results of Monte-Carlo risk probability (MRP) and ORP indicated that workers in petroleum refineries (MRP of 2.9–56% and ORP of 4.6–52% of the affected population) were at a higher risk of adverse health effects from exposure to benzene as compared to exposure to benzene in service station environments (MRP of 0.051 –3.4% and ORP of 0.35–2.7% affected population). The adverse effect risk probabilities estimated by using the Monte-Carlo simulation technique and the ORP method were found to be generally consistent.